Critical parameters investigation of rock breaking by high-pressure foam fracturing method. (1st November 2022) - Cui, Song; Liu, Songyong; Li, Hongsheng; Zhou, Fangyue; Sun, Dunkai
Abstract: As a new and mild rock breaking method between blasting method with high stress loading rate and hydraulic fracturing method with low stress loading rate, high-pressure foam fracturing method has advantages of no spark, less dust, no harmful gas, controllable breaking shape and so on. In this paper, the rock breaking characteristics of 700 × 700 × 700 mm rock samples were studied by using high-pressure foam fracturing device. The influence of borehole depth, seal length and foam pressure on rock breaking were analyzed. The results show that the rock breaking weight increases with an increase of borehole depth and foam pressure, and decreases first and then increases with a decrease of seal length. When the borehole depth is 100–120 mm, the seal length is 30–10 mm and the foam pressure is 15–16.5 MPa, the failure mode of rock changed from blast crater to stripping large stone. These results have certain guiding value for revealing the rock breaking mechanism and engineering application by high-pressure foam fracturing method. Highlights: The analysis of rock breaking characteristics by high pressure foam fracturing. The mechanism of blasting crater of rock. The mechanism of stripping stone.